FAKTOR YANG BERHUBUNGAN DENGAN PERNIKAHAN DINI PADA REMAJA PUTRI DI DESA NANOW KECAMATAN TELUK DALAM: Factors Related To Early Marriage In Adolescent Women In Nanow Village, Telukdalam District - Ina Rahawa; Nurul Mouliza (LPPM - STIKES Pemkab Jombang, 2022)
Background Early marriage is a marriage carried out by someone who is still at an early age or still in his teens. Matchmaking habits still exist in Nias, North Sumatra, because women are not allowed to be close to men, let alone dating. don't know each other. The facts show that 36.7% of early marriages were requested by their parents and 0.9% were forced by their parents to marry. The biggest impact of early marriage and forced marriage is exploitation and violence against women as wives in the household. The purpose of this study was to determine the factors associated with early marriage in adolescent girls in Nanowa Village, Telukdalam District. The purpose of this study was to determine the factors associated with early marriage in adolescent girls in Nanowa Village, Telukdalam District in 2020. The research design used is quantitative method, which is a means to test objective theory by examining the relationship between variables. The method used in this research is a survey with a correlational approach. The population in this study were 110 young women in Nanowa Village, Telukdalam District, the sampling in this study was 52 people using the Slovin formula. Subsequent studies were analyzed using univariate and bivariate data analysis. The results of the study with a chi-square at a=0.05 with a knowledge variable p-value 0.031 (p<0.05), economic p-value 0.000 (p<0.05), social p-value 0.005 (p<0.05), and cultural p-value 0.010 (p<0.05) so that it shows that there is a relationship between knowledge, economy, association and culture with early marriage in adolescents. The conclusion is that there is a relationship between knowledge, economy, association, and culture with early marriage in young women in Nanowa village, Telukdalam sub-distric